Clinical features and outcomes of gastric neuroendocrine tumors after endoscopic diagnosis and treatment: A Digestive Endoscopy Society of Tawian (DEST). Issue 38 (September 2018) - Chung, Chen-Shuan; Tsai, Cho-Lun; Chu, Yin-Yi; Chen, Kuan-Chih; Lin, Jung-Chun; Chen, Bao-Chung; Sun, Wei-Chih; Yen, Hsu-Heng; Chen, Chiung-Yu; Wu, I-Chen; Kuo, Chao-Hung; Shih, Hisang-Yao; et al.
Abstract : Abstract: Gastric neuroendocrine tumors (GNETs) are a heterogeneous group of neoplasm with varying biological characteristics. This study aimed to investigate the clinical features and outcomes of GNET patients after endoscopic diagnosis and treatment in a multicenter registry. Patients with GNETs confirmed histologically were recruited from 17 hospitals between January 2010 and April 2016 in Taiwan. Clinical, laboratory, radiological, endoscopic, pathological data, treatment strategies, follow-up periods, and survivals were collected retrospectively. Totally 187 (107 female, 80 male) patients were recruited. Mean ( ± standard deviation [SD]) age and size of tumors were 63.2-year-old ( ± 14.6) and 2.3-cm ( ± 3.0). World Health Organization (WHO) grading were 93 (49.7%) G1, 26 (13.9%) G2, 40 (21.4%) G3, and 28 (15.0%) unknown. G3 patients were older (mean ± SD, 71.6 ± 12.4 vs. 60.9 ± 14.3/56.7 ± 15.4 years), larger (6.1 ± 4.0 vs.1.2 ± 1.3/2.4 ± 2.5 cm), more distally located (35.0% vs. 7.6%/15.4%), lower proportion of superficial lesions (17.5% vs. 61.9%/53.8%) and higher rates of lymphovascular invasion (32.5% vs. 3.2%/7.7%) than G1/G2. There was no nodal or distant organ metastases despite different grading of lesions≦10 mm and those <20 mm limited to mucosa and submucosa layers. GNETs larger than 20 mm with G1, G2, and G3 had lymph node (LN) metastatic rates of 21.4%, 30.0%, and 59.3%, respectively. Survivals were different between grading for those >20 mm (log-rank test P  = .02). Male gender ( P  = .01), deeper invasion ( P  = .0001), nodal ( P  < .0001), and distant organ metastases ( P  = .0001) were associated with worse outcome. In conclusion, treatment strategies for GNET should be decided by grading, size, invasiveness, and LN metastasis risk. Curative endoscopic resection is feasible for G1/2 lesions less than 20 mm and limited to mucosa/submucosa layers without lymphovascular invasion. Abstract : Supplemental Digital Content is available in the text